Kali Kampwolker Riwayatmu Kini: Suatu Studi Ekoteologi: The Kampwolker River Your Present History: An Ecotheological Study - Notanubun, Kristensia; Nazario Taboka, Julion (MURAI: Jurnal Papua Teologi Konstekstual, 2025)
Human life is inseparable from the condition of the surrounding natural environment. Nature and humans are two sides that mutually depend on each other and should be responsible for maintaining and preserving one another. However, due to population growth and its accompanying needs, humans have exploited the environment for their own benefit. The Kampwolker River is one of the victims of human behavior that no longer respects or preserves its natural surroundings. Ecotheology is used by the authors to examine the relationship between faith, God, and the environment. This study focuses on Christian teachings that can function in ecological awareness and human responsibility toward nature. The research questions are: What are the causes of environmental damage around the Kampwolker River? What are the impacts of environmental damage in the Kampwolker River area? To what extent have concrete actions been taken by the Church, Government, and Local Customs to preserve the environment around the Kampwolker River in Perumnas 3 Waena? The objectives of the research are: 1. To identify the causes of environmental damage around the Kampwolker River. 2. To examine the impact of environmental damage in the Kampwolker River area. 3. To assess the concrete actions taken by the Church, Government, and Local Customs in preserving the environment around the Kampwolker River. The approach used in this research is a descriptive qualitative approach. The research results show that humans are indeed responsible for maintaining nature, but it is the actions of humans that have led to environmental damage. The local community around the Kampwolker River uses nature without maintaining it; trash is dumped in the river, and plantations are established in strategic areas prone to landslides. The community does this because they do not fully understand the long-term impacts on them. The Kampwolker River is the main source of clean water supplied by the Regional Drinking Water Company (PDAM).